2014
DOI: 10.1111/dmcn.12591
|View full text |Cite
|
Sign up to set email alerts
|

Fat distribution in children and adolescents with myelomeningocele

Abstract: AIM To evaluate quantitatively fat distribution in children and adolescents with myelomeningocele using dual-energy X-ray absorptiometry (DXA). METHOD Cross-sectional DXA measurements of the percentage of fat in the trunk, arms, legs, and whole body were compared between 82 children with myelomeningocele (45 males, 37 females; mean age 9y 8mo, SD 2y 7mo; 22 sacral, 13 low lumbar, 47 mid lumbar and above) and 119 comparison children (65 males, 54 females; mean age 10y 4mo, SD 2y 4mo). Differences in fat distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…This is consistent with recent studies, such as the one by Mueske et al 23 Finally, this study found a lower REE compared to predicted energy expenditure and to that of controls, in spite of the fact that both populations had a similar FM%. Polfuss et al8 recently published a literature review to date regarding energy expenditure in myelomeningocele patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with recent studies, such as the one by Mueske et al 23 Finally, this study found a lower REE compared to predicted energy expenditure and to that of controls, in spite of the fact that both populations had a similar FM%. Polfuss et al8 recently published a literature review to date regarding energy expenditure in myelomeningocele patients.…”
Section: Discussionsupporting
confidence: 94%
“…19 Lorenzana et al 20 confirmed an increase in intramuscular fat in the lower limbs, which, although it is a risk factor for metabolic complications compared to subcutaneous fat deposits, may justify an increase in peripheral versus central FM%. Other studies 23 also confirmed peripheral FM localization, particularly in the lower limbs.…”
Section: Discussionsupporting
confidence: 55%
“…It has been shown that up to half of adult patients with myelomeningocele with sacral involvement are not community ambulators [3]. Previous studies have demonstrated that both adult and adolescent patients are more prone to obesity than the general population [4,5]. In addition, they may have abnormal skeletal growth and development due to decreased loading of bones during childhood and adolescence.…”
mentioning
confidence: 99%
“…Este resultado coincidide con estudios recientes, como el estudio citado de Mueske et al 23 Finalmente, en el presente trabajo, se observó menor GER comparado tanto con el gasto energético esperado como con el GER en controles. Esto último, incluso, a pesar de presentar similar %MG entre ambas poblaciones.…”
Section: Discussionunclassified